Analisis Kebijakan Manajemen Risiko Bencana di Daerah Rawan Bencana - Syahwanes, Adnin Chiesa; Saepudin, Eli Apud; Utari, Reviana; Hayatunnisa, Azhar; Ain, Intan Khurotun; Sandy, Masri Ramadillah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Disaster risk management is a systematic effort that aims to reduce the negative impacts of natural and social disasters. In disaster-prone areas, the implementation of disaster risk management policies is crucial to protect communities and critical assets. Disaster-prone areas face complex challenges in managing the risks and impacts of natural disasters that have the potential to threaten the safety and well-being of communities. Disaster risk management combines technical, social and political aspects in mitigation, preparedness, response and recovery efforts against disasters. This research aims to deeply analyse disaster risk management policies implemented in disaster-prone areas, focusing on the conceptual framework, research methodology, empirical findings and relevant policy implications. This research adopts a comprehensive disaster risk management conceptual framework, covering hazard identification, vulnerability analysis, risk assessment, mitigation planning, emergency response and post-disaster recovery. Each component within this framework is described in detail, taking into account interrelated physical, social, economic and environmental factors. This research method uses a multi-method approach that combines qualitative and quantitative methods. Qualitative methods, such as case studies and in-depth interviews, were used to understand stakeholders' perspectives and context.